Disordered Gut Microbiota in Colorectal Tumor-Bearing Mice Altered Serum Metabolome Related to Fufangchangtai - Cai, Mengmeng; Xiao, Ya; Lin, Zhibing; Lu, Jinmiao; Wang, Xiaoyu; Rahman, Sajid Ur; Zhu, Shilan; Chen, Xiaoyu; Gu, Jialin; Ma, Yuzhu; Chen, Zhaoguo; Huo, Jiege (Frontiers in Pharmacology, 2022)
Purpose: This study aimed to investigate the relationship between gut microbes (GM) and serum metabolism using antineoplastic Fufangchangtai (FFCT) as the model prescription in the treatment of colorectal cancer (CRC). Methods: Tumor-bearing and normal mice were administered with different doses of FFCT. The tumor volume of tumor-bearing mice was observed. The levels of CD4+ and CD8+ T cells in blood, spleen and tumor of mice were determined using flow cytometer. The bacterial microbiota in stool samples from mice, and the serum metabolomics of FFCT-treated mice and fecal microbiota transplantation mice were detected using 16s RNA sequencing and liquid chromatography-mass spectrometry (LC/MS), respectively. Results: The tumor volume of mice showed no significant decrease after FFCT intervention. The levels of CD4+ and CD8+T lymphocytes showed a significant increase under the intervention of FFCT. GM of colorectal tumor-bearing mice and healthy mice were determined, and the diversity and abundance of Firmicutes, Deferribacteres, Bacteroidetes and Proteobacteria were significantly different between the two groups. Furthermore, we found that the level of Matrine, Isogingerenone B and Armillaripin were significantly decreased in tumor-bearing mice after FFCT intervention, indicating that the tumor induced dysbiosis of gut bacteria may affect the absorption and metabolism of FFCT. Under the intervention of FFCT, serum metabolism of mice transplanted with fecal from CRC patients showed less metabolites related to FFCT than that from healthy people, indicating that GM could be a single factor to affect the metabolism of FFCT. Further, we found that different doses of FFCT-treated mice had higher abundance of Roseburia, Turicibacter and Flexispira than that in the non-intervention control group. Firmicutes and Bacteroidetes in FFCT-treated groups showed a similar trend with healthy group, indicating that FFCT might correct the intestinal microenvironment by modulating gut microbiota in colorectal tumor-bearing mice. Conclusion: The dysbiosis of GM in tumor-bearing mice reduced the serum metabolites related to FFCT, and FFCT could correct the disordered GM of colorectal tumor-bearing mice to exert efficacy.